Effects of Social Media on Students’ Writing: The Case Study of Mount Mary College of Education - Isaac Anobi Asare; Joseph Dotse Komla Plahar; Ayishetu Pantah; Joana Emefa Adansi (LAFADZ JAYA Publisher, 2022)
The study aimed to determine the impact of social media language (also known as net language) on the formal writing skills of Mount Mary College of Education students. This study involved a total of 150 students, 60 of whom were males and 90 of whom were females, who were studying English language and French at the time of the study. The study employed a phenological research design, and a purposive sample technique was used to choose the thirty (30) participants that took part in it. The responses were mark quiz papers and group tasks, and the results were analysed. The study concluded that when people write individually, social media does have an impact on their formal writing. Students who work in groups, on the other hand, are not affected by this. Another finding of the survey was that respondents employ a wide range of social media lingo, including clipping, abbreviation, alphanumeric homophony, vowel deletion, graphone, and other slang terms, among other things. According to the results of the survey, most people type in social media or internet language when they communicate on social media to make it easier for them to communicate.